RESEARCH ON THE STOCK RETURN IN CHINA-A-SHARE MARKET BASED ON THE FAMA-FRENCH THREE-FACTOR MODEL - WANSHA, CHEN (2022)
This article focused on the applicability of the three-factor model to the Chinese A-share market. The efficiency of the application of the three-factor model to the Chinese financial market was tested by comparing the degree of fit, applicability and explanatory power of the CAPM model and the Fama- French three-factor model under time series in the process of testing the latest empirical data on the A-share market by setting up portfolios with different weighted-average sizes and book-to-market equity.